Optimalisasi Irigasi dengan Sistem Penghalang Sampah Cerdas Berbasis IoT - Muhamad Nanda Abdullah; Muhammad Fariedz Irawan; Ksatria Danuaji; Nur Indah Wulandari Sumarsono; Threea Agung Delta Shafida (Autocracy: Jurnal Otomasi, Kendali, dan Aplikasi Industri, 2025)
Irrigation channels in agricultural areas such as Karawang often experience blockages due to the accumulation of waste and weeds, which consequently disrupt water distribution. To date, the problem has been addressed manually, a method considered neither effective nor efficient. In response to this issue, this study aims to design and assemble an intelligent waste barrier system based on a conveyor mechanism, equipped with an HC-SR04 ultrasonic sensor and an Arduino UNO microcontroller. The system activates when the sensor detects waste, then sends a signal to the Arduino to operate the conveyor. The assembly process was successfully carried out in accordance with the initial design, although further evaluation and refinement are still needed, particularly in adjusting the conveyor speed. This design is expected to serve as an initial step in developing an Internet of Things (IoT)-based solution to address waste blockages in irrigation channels more efficiently and sustainably.